Accelerating the adoption of booster vaccine shots: From the psychological and behavioural perspectives (Journal of Namibian Studies : History Politics Culture, 2023)
Taking booster vaccines plays a critical role to enhance the effectiveness of vaccine programs and their positive externalities to community health. This study treats the booster vaccine as a value and expands the theory of planned behaviour to examine determinants of behaviours to take that value among the public. Mixed research methods are used in this study. While qualitative data from the in-depth interviews support the identification of new themes serving the development of hypotheses and measurement scales, quantitative data from 771 respondents from all walks of life are employed to provide generalized findings. The estimation results indicate five factors that drive the intention to take the booster vaccine shots, including perceived behavioural control, subjective norms, switching costs, communication quality and health concern. More interestingly, results from another follow-up survey about their actual behaviour imply that given the existing intention, those who demonstrate good objective knowledge about booster vaccines are more likely to take the booster shot in practice. These findings draw important implications for policymakers to encourage the behaviour of taking booster vaccines.